THE IMPACT OF THE USAGE OF COMPUTER-ASSISTED TECHNOLOGY (CAT) (Journal of Pharmaceutical Negative Results, 2023)
This paper discusses the suitability of different approaches to computer aided education and to evaluate, discuss methods in language learning study focusing on computer-based language learning field. Several methods are used to investigate how to use computers in a learning process. Computer – assisted technology provide learners with teaching strategies, information, and multimedia platforms to make the learning process easy. However, it does not mean that whole education process replaces traditional education and teachers but improve resources and save time. By which, students can grasp new knowledge and engage themselves at their own pace in a co-relational environment. The purpose of this paper is to distinguish the advantages of computer-centered education.